Prevalence of cancer pain, anxiety and associated factors among patients admitted to oncology ward, Tikur Anbessa Specialized Hospital, Ethiopia, 2019 - Teshome Habte Wurjine; Mekonnen Haftom Goyteom (Open Journal of Pain Medicine - Peertechz Publications, 2020)
Recent study reveals that 2 million people suffer from pain everyday worldwide and cancer pain is one major neglected public health problem especially in Ethiopia. Objective: this study aimed to assess the prevalence of cancer pain and anxiety and associated factors among patients admitted to oncology ward, Tikur Anbesa Specialized Hospital, Addis Ababa, Ethiopia. Methods: An institution based cross-sectional study design was conducted at Tikur Anbesa Specialized Hospital from April 01 to May 7, 2019. Data was collected from the study participants using a semi-structured questionnaire and analyzed by using SPSS software version 23. Binary logistic and multi-variable logistic regression and odds ratio applied to determine the association of variables and P-value <0.05 was considered for statistical significance. Result: The finding of the present study revealed that from a total of 220 respondents involved in this study and about 80% of them had moderate to very severe pain and 62.3% due to cancer lesion. Moreover, only 48.2% used pain management. From the type of cancer; colorectal cancer was the most prevalent cancer type that accounts 49(22.3%) followed by lung cancer 29(13.2%) and about 70(31.8%) of participants were in clinical stage IV. About 54.1% of the respondents waited for more than four months before commencing medical treatment due to overflow of patients. Pain and anxiety were significantly associated. Conclusion and Recommendations: The finding revealed that three fourth of cancer patients suffered from pain and anxiety. It would be better if Tikur Anbesa Specialized Hospital management bodies, researchers and nurses of oncology ward gives more emphasis on pain and anxiety management as priority problems to be managed accordingly.